A hydrophobic magnetic clay sponge material and its preparation method and application

By using magnetic clay in sponge materials to catalyze dopamine hydrochloride polymerization and oxygen-containing silane hydrolysis, hydrophobic magnetic clay sponge materials are prepared, which solves the problems of long preparation time, complex process and high cost of existing materials, and achieves rapid preparation, low cost and high-efficiency adsorption performance of the materials, and imparts magnetic recovery and antibacterial effects.

CN118179457BActive Publication Date: 2025-03-18CHINA UNIV OF GEOSCIENCES (WUHAN)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410242043.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-04
Publication Date
2025-03-18
Estimated Expiration
2044-03-04

AI Technical Summary

Technical Problem

The existing polydopamine-modified hydrophobic sponge materials have problems such as long time, complex modification process and high cost when dealing with marine oil spill accidents. In particular, the use of metal antibacterial substances such as nanosilver has greatly increased its cost.

Method used

Hydrophobic magnetic clay sponge material was prepared by dissolving dopamine hydrochloride in tris(hydroxymethyl)aminomethane-hydrochloric acid buffer solution, adding magnetic clay, alkyl silane and melamine sponge, stirring and drying at high speed. The material catalyzes the dopamine hydrochloride polymerization and oxygen-containing silane hydrolysis through magnetic clay, shortening the preparation time and imparting the material magnetic and hydrophobicity.

Benefits of technology

The rapid preparation, low cost, magnetic recovery and efficient adsorption properties of materials are achieved, and the adsorption organic phase can be selected in the water and oil mixture, and has an antibacterial rate of more than 90% for Staphylococcus aureus.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118179457B_ABST
    Figure CN118179457B_ABST
Patent Text Reader

Abstract

The present invention discloses a hydrophobic magnetic clay sponge material and a preparation method and application thereof. The present invention relates to the technical field of adsorption materials. The present invention dissolves dopamine hydrochloride in a tris(hydroxymethyl)aminomethane-hydrochloric acid buffer solution, then adds magnetic clay, alkylsilane and melamine sponge, stirs at high speed, and obtains a hydrophobic magnetic clay sponge after drying. The present invention uses dopamine polymerization to adhere magnetic clay on melamine sponge and then grafts silane hydrolyzed silica particles, and the obtained hydrophobic magnetic clay sponge material can have sufficient hydrophobicity, antibacterial properties of clay, and magnetic properties, which can be convenient for practical application and recycling, and can be reused.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of adsorption materials, and in particular to a hydrophobic magnetic clay sponge material and a preparation method and application thereof. Background Art

[0002] Marine oil spills cause serious damage to the marine ecological environment. The polluted water is often contaminated by a variety of pathogens, which can spread a variety of infectious diseases and cause serious damage to human health and the ecological environment. Therefore, the treatment of oil spills on the sea surface is quite complicated. In addition to the effective separation of oil and water, the bacterial growth caused by oil spills will still damage the ecological environment.

[0003] The existing polydopamine modified hydrophobic sponge materials are usually used as adsorbent materials and antibacterial materials. Most of the adsorbent materials use the reducibility of dopamine or the hydrophobicity after its hydrophobic modification as a mechanism to adsorb metal ions, dyes or organic matter that pollute water quality; antibacterial materials usually load heavy metal antibacterial substances such as nanosilver to play an antibacterial role. Most of these materials have the common problems of long time consumption and complicated modification process, and the use of metal antibacterial substances such as nanosilver greatly increases their cost. Summary of the invention

[0004] The purpose of the present invention is to provide a hydrophobic magnetic clay sponge material and a preparation method and application thereof in view of the above-mentioned deficiencies in the prior art.

[0005] The invention discloses a method for preparing a hydrophobic magnetic clay sponge material. The method comprises the following steps: dissolving dopamine hydrochloride in a tris(hydroxymethyl)aminomethane-hydrochloric acid buffer solution, adding magnetic clay, alkyl silane and melamine sponge, stirring at a high speed, and drying to obtain a hydrophobic magnetic clay sponge.

[0006] Furthermore, the preparation method of the magnetic clay is as follows: weigh clay and dissolve it in water, then add ferric chloride and stir at high speed until it is uniform, add sodium sulfite, continue stirring until the solution changes from wine red to yellow, add sodium hydroxide, stir, let stand, centrifuge to obtain a precipitate, wash the precipitate with deionized water until it is neutral, and dry to obtain magnetic clay.

[0007] Further, the clay includes one or more of halloysite, montmorillonite, attapulgite, and cordierite;

[0008] And\or, the drying temperature of the magnetic clay obtained by drying is not less than 80°C.

[0009] Furthermore, in step S2, the mass volume ratio of clay to deionized water is 0.1-1g:100mL, the mass ratio of clay to ferric chloride is 0.1-1:1.5, the mass ratio of clay to sodium sulfite is 0.1-1:0.21, and the mass ratio of clay to sodium hydroxide is 0.1-1:1.2.

[0010] Furthermore, the mass ratio of the magnetic clay to dopamine hydrochloride is 0.5:0.05-0.1.

[0011] Furthermore, the mass ratio of the magnetic clay to the melamine sponge is 0.5:0.16-0.2.

[0012] Further, the alkylsilane is one or more of ethyl orthosilicate, polydimethylsiloxane, trimethoxysilane, triethoxysilane, poly(methylhydroxysiloxane), n-dodecyl mercaptan, hexadecyl trimethoxysilane, hexadecyl triethoxysilane, and octadecyl mercaptan;

[0013] And\or, the alkylsilane is tetraethyl silicate and hexadecyltrimethoxysilane;

[0014] and\or, the molar ratio of tetraethyl silicate to hexadecyltrimethoxysilane is 1:1;

[0015] And\or, the drying temperature of the hydrophobic magnetic clay sponge after drying does not exceed 60°C.

[0016] Furthermore, the volume ratio of the alkylsilane to deionized water is 0.75-2:50.

[0017] A hydrophobic magnetic clay sponge material prepared by the preparation method.

[0018] An application of the hydrophobic magnetic clay sponge material as described above in crude oil adsorption and water antibacterial.

[0019] The present invention loads iron elements on clay to prepare magnetic clay. The magnetic clay catalyzes the polymerization process of dopamine hydrochloride and also catalyzes the hydrolysis of oxygen-containing silane, which greatly shortens the preparation time. Unlike other catalysts (catalyzing the polymerization of dopamine hydrochloride), there is no need to recycle and additionally treat the catalyst. The magnetic clay can give the material magnetism, which shortens the process time and gives the adsorption material the ability to be magnetically recovered. In addition, we choose clay with antibacterial properties as the antibacterial agent, which can improve the adsorption capacity of the sponge adsorption material and facilitate modification while reducing the antibacterial cost. Finally, the improved Stober method is selected for hydrophobic modification to make the material selectively adsorbable.

[0020] The present invention uses dopamine polymerization to adhere magnetic clay on a melamine sponge and then grafts silane hydrolyzed silica particles to obtain a hydrophobic magnetic clay sponge material that has sufficient hydrophobicity, antibacterial properties of clay, and magnetic properties, which facilitates practical application and recycling and can be reused.

[0021] The hydrophobic magnetic clay sponge material has excellent selective adsorption and antibacterial properties. It can selectively adsorb the organic phase in the water-oil mixture and can be used for antibacterial purposes. The antibacterial rate of the hydrophobic magnetic clay sponge material against Staphylococcus aureus is more than 90%. It can be directly placed on the polluted water surface to work. After adsorbing the crude oil, the crude oil can be removed by physical squeezing.

[0022] The invention uses clay as the main material, which is rich in resources, low in price, safe and non-toxic; dopamine hydrochloride and melamine sponge are low in price, non-toxic and harmless, and environmentally friendly.

[0023] The present invention adopts a one-pot method to prepare the hydrophobic magnetic clay sponge material, which has mild conditions, simple operation, quick preparation, safety, non-toxicity and low energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a schematic diagram of the polymerization process and structure of dopamine hydrochloride of the present invention.

[0025] Figure 2 This is a SEM (Scanning Electron Microscope) image of the melamine sponge after washing and drying in Example 1 of the present invention.

[0026] Figure 3 The SEM (Scanning Electron Microscope) images of the dopamine / melamine sponge in the blank group of the present invention at different magnifications.

[0027] Figure 4 These are SEM (Scanning Electron Microscope) images of the magnetic halloysite / dopamine / hydrophobic melamine sponge adsorption material in Example 1 of the present invention at different magnifications.

[0028] Figure 5 This is a static water contact angle diagram of the magnetic halloysite / dopamine / hydrophobic melamine sponge adsorption material in Example 1 of the present invention.

[0029] Figure 6 This is a colony diagram of the antibacterial rate of the magnetic halloysite / dopamine / hydrophobic melamine sponge adsorption material in Example 1 of the present invention. DETAILED DESCRIPTION

[0030] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.

[0031] The present invention also provides a method for preparing the hydrophobic magnetic clay sponge material, comprising the following steps:

[0032] Step S1, cutting the melamine sponge into blocks, then washing with deionized water and anhydrous ethanol in sequence, and drying for later use;

[0033] Step S2, weighing clay and dissolving it in water, then adding ferric chloride and stirring at high speed until uniform, adding sodium sulfite, and continuing to stir until the solution changes from wine red to yellow, adding sodium hydroxide, stirring, standing, and centrifuging to obtain a precipitate, washing the precipitate with deionized water until it is neutral, and drying to obtain magnetic clay;

[0034] Step S3, weighing dopamine hydrochloride and dissolving it in a tris(hydroxymethyl)aminomethane-hydrochloric acid buffer solution with a pH of 8, adding magnetic clay, adding alkyl silane, adding melamine sponge, stirring at high speed for 10-180 minutes, and drying;

[0035] Step S4, washing the dried sponge with deionized water, and drying to obtain a magnetic clay / dopamine / hydrophobic melamine sponge, i.e., a hydrophobic magnetic clay sponge material.

[0036] The following clay is taken as an example of halloysite; the alkyl silane is taken as an example of tetraethyl silicate and hexadecyltrimethoxysilane; and the hydrophobic magnetic clay sponge material and the preparation method thereof of the present invention are described in detail in conjunction with the embodiments.

[0037] Blank Group

[0038] Preparation of polydopamine / melamine sponge

[0039] Cut the melamine sponge into cubes of 2*2*0.5cm, then wash with deionized water and anhydrous ethanol alternately, and dry at 60℃. Weigh 0.03g of tris(hydroxymethyl)aminomethane, dissolve it in 50mL of deionized water, and titrate it with dilute hydrochloric acid to pH=8 to prepare tris(hydroxymethyl)aminomethane-hydrochloric acid buffer solution (Tris buffer solution). Weigh 0.05g of dopamine hydrochloride, add 50mL of Tris buffer solution, add 4 washed melamine sponges, stir for 24h, and dry at 60℃ to obtain polydopamine / melamine sponge.

[0040] Example 1

[0041] Cut the melamine sponge into 2*2*0.5cm cubes, then wash alternately with deionized water and anhydrous ethanol, and dry at 60℃. Take 1.0g of halloysite and dissolve it in 100mL of deionized water, then add 1.5g of ferric chloride, stir for 15min until uniform, add 0.21g of sodium sulfite solution and the color turns wine red, continue stirring until the solution turns yellow, then weigh 1.2g of sodium hydroxide and add it to the solution, and continue stirring for 15min. Use a magnet to aggregate the black precipitate, use a centrifuge to extract it, wash the precipitate with deionized water after centrifugation, repeat the centrifugation until the supernatant is neutral, dry and grind at 80℃ to obtain magnetic halloysite.

[0042] Weigh 0.03g of tris(hydroxymethyl)aminomethane, dissolve it in 50mL of deionized water, and titrate it with dilute hydrochloric acid to pH=8 to prepare tris(hydroxymethyl)aminomethane-hydrochloric acid buffer solution (Tris buffer solution). Weigh 0.05g of dopamine hydrochloride, add it to 50mL of Tris buffer solution, add 0.5g of magnetic halloysite and 4 washed melamine sponges, add 0.5mL of tetraethyl silicate and 1.0mL of hexadecyltrimethoxysilane, stir for 30min, and dry at 60℃.

[0043] The mixture was then washed with anhydrous ethanol for three times and dried at 60° C. to obtain a magnetic halloysite / dopamine / hydrophobic melamine sponge adsorption material, namely a hydrophobic magnetic clay sponge material.

[0044] Figure 1 2 is a schematic diagram of the polymerization process and structure of dopamine hydrochloride of the present invention.

[0045] Example 2

[0046] Cut the melamine sponge into 2*2*0.5cm cubes, then wash with deionized water and anhydrous ethanol alternately, and dry at 60℃. Take 1.25g of halloysite and dissolve it in 100mL of deionized water, then add 1.5g of ferric chloride, stir for 15min until it is uniform, add 0.21g of sodium sulfite solution until the color turns wine red, continue to stir until the solution turns yellow, then weigh 1.2g of sodium hydroxide and add it to the solution, and continue to stir for 15min. Use a magnet to aggregate the black precipitate, use a centrifuge to extract it by centrifugation, wash the precipitate with deionized water after centrifugation, repeat the centrifugation until the supernatant is neutral, dry and grind at 80℃ to obtain magnetic halloysite.

[0047] Weigh 0.03g tris(hydroxymethyl)aminomethane, dissolve it in 50mL deionized water, and titrate it with dilute hydrochloric acid to pH=8 to prepare tris(hydroxymethyl)aminomethane-hydrochloric acid buffer solution (Tris buffer solution). Weigh 0.05g dopamine hydrochloride, add it to 50mL Tris buffer solution, add 0.75g magnetic halloysite and 5 washed melamine sponges, add 0.5mL tetraethyl silicate and 1.0mL hexadecyltrimethoxysilane, stir for 30min, and dry at 60℃.

[0048] The mixture was then washed with anhydrous ethanol for three times and dried at 60° C. to obtain a magnetic halloysite / dopamine / hydrophobic melamine sponge adsorption material, namely a hydrophobic magnetic clay sponge material.

[0049] Example 3

[0050] Cut the melamine sponge into 2*2*0.5cm cubes, then wash with deionized water and anhydrous ethanol alternately, and dry at 60℃. Take 1.0g of halloysite and dissolve it in 100mL of deionized water, then add 1.5g of ferric chloride, stir for 15min until it is uniform, add 0.21g of sodium sulfite solution until the color turns wine red, continue to stir until the solution turns yellow, then weigh 1.2g of sodium hydroxide and add it to the solution, and continue to stir for 15min. Use a magnet to aggregate the black precipitate, use a centrifuge to extract it by centrifugation, wash the precipitate with deionized water after centrifugation, repeat the centrifugation until the supernatant is neutral, dry and grind at 80℃ to obtain magnetic halloysite.

[0051] Weigh 0.03g of tris(hydroxymethyl)aminomethane, dissolve it in 50mL of deionized water, and titrate it with dilute hydrochloric acid to pH=8 to prepare tris(hydroxymethyl)aminomethane-hydrochloric acid buffer solution (Tris buffer solution). Weigh 0.05g of dopamine hydrochloride, add it to 50mL of Tris buffer solution, add 0.5g of magnetic halloysite and 4 washed melamine sponges, dropwise add 1.0mL of tetraethyl silicate and 1.0mL of hexadecyltrimethoxysilane, stir for 30min, and dry at 60℃.

[0052] The mixture was then washed with anhydrous ethanol for three times and dried at 60° C. to obtain a magnetic halloysite / dopamine / hydrophobic melamine sponge adsorption material, namely a hydrophobic magnetic clay sponge material.

[0053] Example 4

[0054] The mass volume ratio (g / ml) of magnetic clay and alkyl silane in Example 1 was changed, and the hydrophobic magnetic clay sponge material was prepared in the same manner as in Example 1, and then the hydrophobicity test was conducted on each hydrophobic magnetic clay sponge material. The experimental results are as follows:

[0055] Table 1 Hydrophobicity experimental results of hydrophobic magnetic clay sponge material prepared in Example 4

[0056]

[0057] From the above data, it can be seen that the mass ratio (g / ml) of magnetic clay to alkyl silane is more suitable at 0.5:0.75-2.

[0058] Example 5

[0059] The type and ratio of the alkylsilane in Example 1 were changed, and the hydrophobic magnetic clay sponge materials were prepared in the same manner as in Example 1. Then, the hydrophobicity test was conducted on each hydrophobic magnetic clay sponge material. The experimental results are as follows:

[0060] Table 2 Hydrophobicity experimental results of hydrophobic magnetic clay sponge material prepared in Example 5

[0061]

[0062] Comprehensive data show that tetraethyl silicate can promote the hydrolysis of hexadecyltrimethoxysilane better than single alkyl silane, and the direct molar ratio of different alkyl silanes is best at 1:1.

[0063] Example 6

[0064] The hydrophobic magnetic clay sponge material was prepared in the same manner as in Example 1 except that the mass ratio of clay to dopamine hydrochloride in Example 1 was changed.

[0065] Table 3 Example 6 Preparation of hydrophobic magnetic clay sponge material phenomenon table

[0066]

[0067] In order to maximize the product yield, the melamine sponge is maintained at 0.2g, the mass of dopamine hydrochloride is above 0.05g, and the mass ratio of clay and dopamine hydrochloride is changed after ensuring the polymerization effect. From 6.1 to 6.3, it can be seen that the clay exceeds 0.5g at 6.3, resulting in too much white clay in the solution and the color becomes lighter. From 6.4 and 6.5, it can be seen that after the clay 0.5g dopamine hydrochloride exceeds 0.1g, it begins to be excessive, causing the color of the solution to darken again. Comprehensive data show that the mass ratio of clay to dopamine hydrochloride (g / g) is more suitable at 0.5:0.05-0.1.

[0068] The magnetic halloysite / dopamine / hydrophobic melamine sponge prepared in Example 1 was subjected to an organic matter adsorption experiment. The sample was weighed, immersed in a pure solution and allowed to stand for 3 minutes of adsorption, then taken out and weighed, and after weighing, the solution was squeezed out and immersed again and the experiment was repeated three times. The adsorption amount (g / g) was calculated as follows:

[0069]

[0070] Where m0 represents the net weight of the sample, mn Represents the weight of the sample after the nth adsorption.

[0071] Table 3: Adsorption capacity of pure organic solvent by the hydrophobic magnetic clay sponge material prepared in Example 1 (m n is the weight after the nth adsorption)

[0072]

[0073] The hydrophobic magnetic clay sponge material prepared in Example 1 was subjected to an inhibition zone and inhibition rate experiment of Staphylococcus aureus. Staphylococcus aureus was inoculated in 15 mL of liquid culture medium, cultured at 37 ° C, 150 r / min for 8 h; then 200 uL of the suspended bacterial solution was transferred to 15 mL of liquid culture medium with a pipette, and cultured in a shaker at 37 ° C, 150 r / min for 8 h to obtain a second-generation suspended bacterial solution. The second-generation suspended bacterial solution was centrifuged at 5000 r / min for 10 min, the supernatant was removed, and the precipitate was diluted to CFU / mL and CFU / mL using a ten-fold gradient dilution method with a sterilized PBS buffer. Take 3mL of CFU / mL bacterial solution and put it into a centrifuge tube. Then put the samples of the control group and the experimental group into the centrifuge tube and culture them in a shaker at 37℃ and 150r / min for 18h. Then take 100uL of the diluted bacterial solution and apply it on the culture medium. Incubate it upside down in a 37℃ incubator for 24h. Then count the number of colonies on each culture medium and calculate the inhibition rate. The calculation formula of the inhibition rate is:

[0074]

[0075] Where: R represents the inhibition rate, B0 represents the number of colonies on the culture medium of the control group, and Bt represents the number of colonies on the culture medium of the experimental group.

[0076] Table 2: Inhibition zone and inhibition rate of Staphylococcus aureus by the hydrophobic magnetic clay sponge material prepared in Example 1

[0077]

[0078] Figure 2 The SEM (Scanning Electron Microscope) images of the melamine sponge after washing and drying in Example 1 at different magnifications are shown in FIG. Figure 2 a is a SEM image of melamine sponge magnified at 2.2k. Figure 2 b is the SEM image of melamine sponge magnified at 4.4k. Figure 2 c is the SEM image of melamine sponge magnified at 11k. Figure 2 d is the SEM image of melamine sponge magnified at 22k. Figure 2It can be seen that after alternating washing with deionized water and ethanol, the interior of the melamine sponge has become very clean. The melamine sponge has a complex multi-level pore structure, which gives it a relatively large specific surface area, resulting in more adsorption sites and higher adsorption efficiency.

[0079] Figure 3 These are SEM (Scanning Electron Microscopr) images of the dopamine / melamine sponge of the blank group of the present invention at different magnifications. Figure 3 a is a SEM image of dopamine / melamine sponge magnified at 2.2k. Figure 3 b is the SEM image of dopamine / melamine sponge at 4.4k magnification. Figure 3 c is the SEM image of dopamine / melamine sponge magnified at 11k. Figure 3 d is the SEM image of dopamine / melamine sponge at 22k magnification. Figure 3 It can be seen that by polymerizing dopamine hydrochloride on the surface of the sponge, a polymer layer composed of polydopamine can be formed on the surface of the internal frame of the sponge.

[0080] Figure 4 These are SEM (Scanning Electron Microscope) images of the magnetic halloysite / dopamine / hydrophobic melamine sponge adsorption material in Example 1 of the present invention at different magnifications. Figure 4 a is a SEM image of magnetic halloysite / dopamine / hydrophobic melamine sponge at 2.2k magnification. Figure 4 b is a SEM image of magnetic halloysite / dopamine / hydrophobic melamine sponge at 4.4k magnification. Figure 4 c is the SEM image of magnetic halloysite / dopamine / hydrophobic melamine sponge at 11k magnification. Figure 4 d is a SEM image of magnetic halloysite / dopamine / hydrophobic melamine sponge at 22k magnification. Figure 4 It can be seen that polydopamine successfully adheres halloysite to the inside of the melamine sponge, and further zooming in shows that a thin film of silane hydrolysis products that is finer than polydopamine is formed on the surface of the internal framework of melamine after the hydrolysis of oxygen-containing silane and is evenly distributed. Even though the SEM image is somewhat distorted due to the magnetism of the sample, it can still be roughly seen that a layer of material has been successfully adhered to the internal structure of the sponge, proving the successful polymerization of dopamine.

[0081] Figure 5 : is a static water contact angle diagram of the magnetic halloysite / dopamine / hydrophobic melamine sponge adsorption material in Example 1 of the present invention. Figure 5It can be seen that the water contact angle of the magnetic halloysite / dopamine / hydrophobic melamine sponge adsorbent material is much greater than 90°, indicating that the magnetic halloysite / dopamine / hydrophobic melamine sponge adsorbent material has good hydrophobicity.

[0082] Figure 6 1 is a colony diagram of the antibacterial rate experiment of the magnetic halloysite / dopamine / hydrophobic melamine sponge adsorption material (right figure) and the blank group dopamine / melamine sponge (left figure) in Example 1 of the present invention. Figure 6 It can be seen that the magnetic halloysite / dopamine / hydrophobic melamine sponge adsorption material has a good antibacterial effect.

[0083] For matters not mentioned above, the prior art applies.

[0084] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a hydrophobic magnetic clay sponge material, characterized in that: Dissolving dopamine hydrochloride in a tris(hydroxymethyl)aminomethane-hydrochloric acid buffer solution, then adding magnetic clay, alkyl silane and melamine sponge, stirring at high speed, and drying to obtain a hydrophobic magnetic clay sponge; Weigh clay and dissolve it in water, then add ferric chloride and stir at high speed until it is uniform, add sodium sulfite and continue stirring until the solution changes from wine red to yellow, add sodium hydroxide, stir, stand, centrifuge to obtain a precipitate, wash the precipitate with deionized water until it is neutral, and dry to obtain magnetic clay; The clay includes one or more of halloysite, montmorillonite, attapulgite, and cordierite; The alkylsilane is one or more of ethyl orthosilicate, polydimethylsiloxane, trimethoxysilane, triethoxysilane, polymethylhydroxysiloxane, n-dodecyl mercaptan, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, and octadecyl mercaptan.

2. The method for preparing a hydrophobic magnetic clay sponge material according to claim 1, characterized in that: The drying temperature of the magnetic clay obtained by drying is not less than 80°C.

3. A method for preparing a hydrophobic magnetic clay sponge material according to claim 1 or 2, characterized in that: The mass volume ratio of clay to deionized water is 0.1-1 g: 100 mL, the mass ratio of clay to ferric chloride is 0.1-1: 1.5, the mass ratio of clay to sodium sulfite is 0.1-1: 0.21, and the mass ratio of clay to sodium hydroxide is 0.1-1: 1.

2.

4. The method for preparing a hydrophobic magnetic clay sponge material according to claim 1, characterized in that: The mass ratio of the magnetic clay to dopamine hydrochloride is 0.5:0.05-0.

1.

5. The method for preparing a hydrophobic magnetic clay sponge material according to claim 1, characterized in that: The mass ratio of the magnetic clay to the melamine sponge is 0.5:0.16-0.

2.

6. The method for preparing a hydrophobic magnetic clay sponge material according to claim 1, characterized in that: The alkylsilanes are tetraethyl silicate and hexadecyltrimethoxysilane; and\or, the molar ratio of tetraethyl silicate to hexadecyltrimethoxysilane is 1:1; And\or, the drying temperature of the hydrophobic magnetic clay sponge after drying does not exceed 60°C.

7. The method for preparing a hydrophobic magnetic clay sponge material according to claim 1, characterized in that: The volume ratio of the alkylsilane to deionized water is 0.75-2:

50.

8. A hydrophobic magnetic clay sponge material prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the hydrophobic magnetic clay sponge material as claimed in claim 8 in crude oil adsorption and water antibacterial.

Citation Information

Patent Citations

  • Making method and use of silica constructed superhydrophobic melamine sponge

    CN107245159A

  • Preparation method of super-hydrophobic super-oleophylic polymer sponge material

    CN113980347A